2009
DOI: 10.1590/s1135-57272009000200015
|View full text |Cite
|
Sign up to set email alerts
|

Relación en España de la duración de la gestación y del peso al nacer con la nacionalidad de la madre durante el período 2001-2005

Abstract: Results of LBW and PB were more favourable in the births of immigrant women. It could be associated with the healthy migrant effect and a low frequency of risk practices during gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
2
12
2
1
Order By: Relevance
“…All groups show a lower risk of LBW with the exceptions of EU-15 and USA & Canada, with no conclusive differences, and sub-Saharan Africa, who show a significantly higher risk. These results support previous evidence in Spain for most groups29 30 and a disadvantage for babies of sub-Saharan descent 30 31. The advantage is also observed among LBW at term babies (proxy of babies with intrauterine growth restriction).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…All groups show a lower risk of LBW with the exceptions of EU-15 and USA & Canada, with no conclusive differences, and sub-Saharan Africa, who show a significantly higher risk. These results support previous evidence in Spain for most groups29 30 and a disadvantage for babies of sub-Saharan descent 30 31. The advantage is also observed among LBW at term babies (proxy of babies with intrauterine growth restriction).…”
Section: Discussionsupporting
confidence: 90%
“…For gestational age, however, we find a higher risk of preterm birth for groups who had shown advantages in earlier studies (period before 2006),30 31 such as South America, the Caribbean and EU-Extension. The pattern we observe seems consistent over very (<32 gestational weeks) and moderate preterm (>32 gestational weeks and <37 gestational weeks) (data not shown in tables).…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“… reported a significant association between the presence of periodontal disease and PTB, with an adjusted OR of 1.77. Again in this study the population assayed was different, since it included only a 78% of Caucasian women and mainly of low social, economic and educational level, reporting a prevalence of PTB of 6.6%, higher than in our study, but more similar to the epidemiological figures reported for the general population in Spain (7.9% in 2001–2005) . Moreu et al .…”
Section: Discussionsupporting
confidence: 46%
“…Infants born to immigrant women in the US, Belgium, and France had lower risks of low birth weight compared to the native-born population [22,23]. In a Spanish study immigrant infants showed lower risks of low birth weight and prematurity compared to those of native-born women [24]. Such contrasting evidence may be explained by different access and referral to healthcare services [8,13,25], and by different integration policies in the host countries [11].…”
Section: Introductionmentioning
confidence: 99%